Impact of Isolated Tricuspid Valve Repair on Right Ventricular Remodelling in an Adult Congenital Heart Disease Population - Marsico, Roberto; Bruno, Vito Domenico; Chivasso, Pierpaolo; Baritussio, Anna; Rapetto, Filippo; Guida, Gustavo A.; Benedetto, Umberto; Caputo, Massimo (Frontiers in Cardiovascular Medicine, 2017)
Background: Surgical repair of isolated congenital tricuspid valve (TV) disease is rare with no well-defined indication and outcomes. Moreover, the role of right ventricle (RV) in this context has not yet been investigated. Objectives: We sought to assess the impact of congenital TV repair on cardiac remodelling and clinical-functional status and the importance of the RV function in an adult congenital heart disease (ACHD) population. Methods and Results: From January 2005 to December 2015, 304 patients underwent TV surgery in our centre. Of these, 27 (ACHD) patients had isolated TV repair. Patients were evaluated with preoperative and post-operative trans-thoracic echocardiogram. Survival rate has been investigated with a mean clinical follow-up of 3.7 ± 2.3 years while the mean echocardiographic follow-up was 2.9 ± 1.8 years. The clinical and functional status of patients showed a statistically significant improvement after the surgical repair in terms of NYHA class (66.7% vs 7.4%; p <0.01), clinical signs of heart failure (29.6%; vs 7.4%; p <0.01) and left ventricular function (14.8% vs 7.4%; p <0.01). The RV and right atrium (RA) diameter were significantly reduced after surgery (5.15 ± 1.21 vs 4.32 ± 1.16 p <0.01) and (44.7 ± 16.7 vs 26.7 ± 9.2; p <0.01) respectively. The degree of postoperative pulmonary hypertension was also significantly reduced (40.7% vs 7.4%; p <0.01). The survival rate was 96.3% at 1 year and 93.7% at 5 years. One patient (3.7%) had early failure of the tricuspid repair requiring a re-operation. Conclusion: Isolated tricuspid valve repair for adult congenital disease significantly improved patients’ clinical and functional status and allowed right ventricular remodelling and functional improvement.